Anti-Galician Sentiment and Propaganda: Galicia and the Galicians in the Chronicles at the Service of the Catholic Monarchs - Peres Vigo, Alexandre (Madrygal. Revista de Estudios Gallegos, 2023)
From the first half of the 15th century onwards, the position of chronicler acquired a growing relevance in the Castilian court. However, it was during the reign of the Catholic Monarchs when this genre emerged strongly as one of the main ideological and propagandistic pillars at the service of the crown. Chroniclers, being those responsible for providing an official and apologetic narrative of the reign, created a whole literary corpus to glorify the memory of the monarchs and also to support the very legitimacy of Isabella I, as well as the authoritarian political project carried out by the royal couple. This paper analyses the propagandistic discourse which is to be found in the royal chronicles and which was used to relate the political and military actions undertaken by the Catholic Monarchs in the Kingdom of Galicia, as well as the indications of an emerging anti-Galician sentiment (Gallaecophobia), which mobilised a clichéd image of the kingdom and an anti-Galician stereotype as means to justify the said actions.